Development of ITER relevant ICRF wall conditioning technique on European tokamaks - Lyssoivan, A.; Koch, R.; Van Eester, D.; Vervier, M.; Weynants, R.; Esser, H.G.; Philipps, V.; Gauthier, E.; Hartmann, D.A.; Noterdaeme, J.-M.; Bobkov, V.; Braun, F.; et al. (Вопросы атомной науки и техники, 2005)
In future reactor-scale superconducting fusion devices such as ITER, the presence of a permanent high magnetic field will prevent the use of conventional Glow Discharge Conditioning in between shots. Therefore, only discharges fully compatible with the presence of high magnetic field can be used for the conditioning procedure. ICRF discharge has a high potential to solve this problem. The paper presents a review of the new ICRF wall conditioning technique developed on limiter tokamaks TEXTOR and TORE SUPRA and the results of the first tests on the divertor tokamaks ASDEX Upgrade and JET. У майбутніх термоядерних установках зі надпровідними магнітними системами масштабу ИТЕРа присутність постійного сильного магнітного поля буде перешкоджати використанню звичайних тліючих розрядів для підготовки вакуумних стінок між розрядами. Тому тільки розряди, що працюють при сильному магнітному полі, можуть бути використані для цих цілей. ВЧ розряди в області частот ІЦР мають великий потенціал для рішення цієї проблеми. У даній роботі представлений огляд нових ВЧ ІЦРтехнік підготовки стінок, розвитих на токамаках з лімітером TEXTOR і TORE SUPRA і результати перших іспитів на токамаках з дивертором ASDEX UPGRADE іJET. В будущих термоядерных установках с сверхпроводящими магнитными системами масштаба ИТЕРа присутствие постоянного сильного магнитного поля будет препятствовать использованию обычных тлеющих разрядов для подготовки вакуумных стенок между разрядами. Поэтому только разряды, работающие при сильном магнитном поле, могут быть использованы для этих целей. ВЧ разряды в области частот ИЦР обладают большим потенциалом для решения этой проблемы. В настоящей работе представлен обзор новых ВЧ ИЦР техник подготовки стенок , развитых на токамаках с лимитером TEXTOR и TORE SUPRA и результаты первых испытаний на токамаках с дивертором ASDEX UPGRADE и JET.